2015
DOI: 10.1590/1982-43272562201510
|View full text |Cite
|
Sign up to set email alerts
|

Evidences of Factorial Structure and Precision of Phonemic Awareness Tasks (TCFe)

Abstract: Abstract:To assess phonological awareness -a decisive skill for learning to read and write -it is necessary to provide evidence about an instrument construct to present trustworthy parameters for both empirical research and the development of educational intervention and rehabilitation programs. In Brazil, at this moment, there are no studies regarding the internal structure for tests of phonological awareness. This article shows the factorial validity of a test of phonological awareness composed by three subt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
7
0
2
Order By: Relevance
“…The last two tasks were adapted for use in BP by Godoy (2001) from battery BELEC (Mousty, Leybaert, Alegria, Content, & Morais, 1994). Further study demonstrated the factorial structure validity of the segmentation and subtraction phonemic tasks (Godoy & Cogo-Moreira, 2015). Phonemic segmentation.…”
Section: Methodsmentioning
confidence: 89%
“…The last two tasks were adapted for use in BP by Godoy (2001) from battery BELEC (Mousty, Leybaert, Alegria, Content, & Morais, 1994). Further study demonstrated the factorial structure validity of the segmentation and subtraction phonemic tasks (Godoy & Cogo-Moreira, 2015). Phonemic segmentation.…”
Section: Methodsmentioning
confidence: 89%
“…Regarding studies conducted with Brazilian Portuguese speakers, to our knowledge, three studies investigated the factorial structure of different measures of phonological awareness: Godoy and Cogo-Moreira (2015); Santos and Lima (2017); and Germano, César, and Capellini (2017). The study by Godoy and Cogo-Moreira (2015) included three measures of phonemic awareness (phoneme segmentation, onset deletion in nonwords with a consonant-vowel-consonant [CVC] structure, and onset deletion in nonwords with a consonant-consonant-vowel [CCV] structure); this study was conducted with 176 Brazilian 1 st to 5 th graders. The researchers assessed the fit of the data to a model in which the items of each of the three phonological awareness measures represented different factors that were correlated (segmentation, CVC deletion, and CCV deletion).…”
Section: Studies With Brazilian Portuguesementioning
confidence: 99%
“…Considering the divergence among the results from studies on the dimensionality of phonological awareness conducted thus far in Brazil (Germano et al, 2017;Godoy and Cogo-Moreira, 2015;Santos and Lima, 2017), and internationally (Anthony et al, 2002(Anthony et al, , 2011Hatcher and Hulme, 1999;Papadopoulos et al, 2012;Runge and Watkins, 2006;Schatschneider et al, 1999;Vloedgraven and Verhoeven, 2009;Wagner et al, 1997;Wagner et al, 1994;Wolff and Gustafsson, 2015), we aim to investigate this issue. The present study included measures that differ in their cognitive demand (detection, blending, segmentation, and deletion) and the phonological unit (rhyme, syllable, and phoneme).…”
Section: The Present Studymentioning
confidence: 99%
“…Three instruments were used to assess reading: the Teste de Desempenho Escolar (TDE, School Performance Test), isolated word reading test (Stein, 1994), the Prova de Avaliação dos Processos de Leitura (PROLEC, Assessment of reading processes) (reading test and understanding of small texts, Capellini, Oliveira, & Cuetos, 2014), and the Teste de Leitura: Compreensão de Sentenças (TELCS, Reading Test: Understanding Sentences) (Test of reading and understanding sentences, Vilhena, Sucena, Castro, & Pinheiro, 2016). To assess phonemic awareness, the Tarefas de Consciência Fonêmica (TCFe, Phonemic Awareness Tasks) by Godoy and Cogo-Moreira (2015) were used. To assess executive functions, some subtests of the Instrumento de Avaliação Neuropsicológica Breve (Neupsilin-inf Brief, Neuropsychological Assessment Instrument for Child) neuropsychological battery (working memory, inhibitory control and verbal fluency) (Salles et al, 2016), the Trails test (Montiel & Seabra, 2012b), the Cancellation, and the Tower of London test were used, as described in Chart 1.…”
Section: Instrumentsmentioning
confidence: 99%